Komparasi Kinerja Turbin Angin Sumbu Vertikal Darrieus Tipe- H Dengan Bilah Profil NACA 0018 Dengan dan Tanpa Wind Deflector - Indra Herlamba Siregar (Department of Mechanical Engineering Atma Jaya Catholic University of Indonesia, 2014)
The length of 80791.42 km coastline Indonesia is a potential area for the development of wind energy with wind speeds average is generally between 3 m / s to 5 m/s, the total wind energy potential is estimated to reach 9 GW. However, the geographical Indonesia as a tropical country has characteristics of wind direction in Indonesia frequent changes, which condition is causing the sustainability of energy production from horizontal axis wind turbine rotor turbine disrupted due must always deal with the arrival of the wind direction. It required the design of the turbine according to the characteristics and the wind speed in Indonesia. In the present study to see the effect of adding wind deflector on the performance of vertical axis wind turbine models Darrieus type-H blades with NACA 0018 profile of the tested wind speed 2.86 m / s and 3.43 m / s and a pitch angle of 150, 200, 250 and 300 with a load of 200, 250 and 300 gr. The results presented that the addition of wind deflector can improve the performance of vertical axis wind turbines Darrius type-H in the form of 56.37% power turbine and turbine performance coefficient of 65.03% on the pitch angle 300 at wind speed 3.43 m / s